PENINGKATAN PERTUMBUHAN DAN HASIL BAWANG MERAH (Allium ascalonicum, L) DENGAN APLIKASI PERBEDAAN KONSENTRASI BIO SLURRY DAN PEMOTONGAN UMBI BIBIT - pramono hadi hadi (Agroplantae: Jurnal Ilmiah Terapan Budidaya dan Pengelolaan Tanaman Pertanian dan Perkebunan, 2021)
ABSTRACT This study aims to determine the effect of bio slurry and cutting of seed tubers on the growth and yield of shallot plants in the Dukuh Kepoh Food and Horticultural Garden, Tohudan Village, Colomadu District, Karanganyar Regency with a height of ± 105 m above sea level, from April until June 2020. This study used a factorial method with a complete randomized block design (RAKL), consisting of two treatment factors, while the two treatment factors with 12 treatment combinations, each treatment was repeated (3) times. The first treatment, the concentration of bio slurry (S) which consists of 4 levels, namely (S1: Bio slurry 0 ml / l, S2: Bio slurry 50 ml / l, S3: Bio slurry 100 ml / l, S4: Bio slurry 150 ml / l). The second treatment was cutting the seed tubers (P), which consisted of three levels (P1: Cutting 1/4 part of seed tubers, P2: Cutting 1/3 parts of seed tubers, P3: Cutting 1/2 parts of seed tubers). The results showed that the treatment with bio slurry (S) had no significant effect on all observed parameters. Treatment by cutting seed tubers (P) had a very significant effect on plant height, weight of fresh tubers per plant, weight of fresh tubers per plot and had a significant effect on the number of fresh tubers per plant, but had no significant effect on the number of tubers per plot and weight of fresh stems. The combination between the treatment of bio slurry and cutting of seed tubers (SxP) did not significantly affect all observed parameters, The highest yield of fresh tubers per plot was obtained in treatment (S2P2) with a yield of 800.00 g, while the lowest tuber weight per plot was obtained in treatment ( S1P3) with a yield of 433.33 g. Keywords: shallot, bio-slurry, seed tuber cutting